2020
DOI: 10.1177/1934578x20971469
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemical Compositions of the Pepper EOs From Different Cultivars and Their AChE Inhibitory Activity

Abstract: Pepper is one of the most popular spices over the world and is called the King of Spices. Its essential oils (EOs) could alleviate neuronal ailments due to the inhibitory effect against acetylcholinesterase (AChE). In this study, the chemical compositions of 26 EOs prepared from white and black pepper collecting from 6 different cultivars were analyzed by gas chromatography-mass spectrometry (GC-MS). A total of 133 compounds were identified in the white and black pepper EOs. Monoterpenes and sesquiterpenes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The presence of limonene, β-caryophyllene, and 3-carene was common in both HDO and CPO. Chen et al (2020) reported that 3-carene could be used as a quality marker of black pepper oil for evaluating its inhibitory activity against acetylcholinesterase enzyme [ 37 ]. Thus, the abovementioned compounds may be potential markers in the quality control analysis of pepper oil.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of limonene, β-caryophyllene, and 3-carene was common in both HDO and CPO. Chen et al (2020) reported that 3-carene could be used as a quality marker of black pepper oil for evaluating its inhibitory activity against acetylcholinesterase enzyme [ 37 ]. Thus, the abovementioned compounds may be potential markers in the quality control analysis of pepper oil.…”
Section: Discussionmentioning
confidence: 99%
“…Among plant secondary metabolites, essential oils (EOs), biosynthesized by glandular trichomes and other secretory structures in plants, are liquids particularly rich in volatile molecules such as monoterpene and sesquiterpene hydrocarbons, oxygenated monoterpenes and sesquiterpenes, esters, aldehydes, ketones, alcohols, phenols, and oxides [ 2 , 3 , 4 ]. The chemical composition of EOs can vary from plant to plant and even in the same species and depends on several factors such as post-harvest conservation conditions [ 5 ], extraction methods [ 6 , 7 , 8 ] and times [ 9 , 10 ], microclimate, and site in which the plant is growing [ 11 , 12 ]. EOs contribute to the plant relations with environment and with other organisms, and humans and animals take advantage of the abundance of such bioactive molecules from the plant kingdom [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Investigated black pepper from the Yunnan Province in China contained 4.12%, and white pepper contained 3.01% of essential oil. On the other hand, the content of essential oil obtained from pepper originating in Indonesia and Vietnam was at the level of approximately 2% [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…A very important ingredient of black pepper is oleoresin, derived by extraction in the amount of 6–13%. It consists of 15–20% of essential oil and 35–55% piperine [ 24 , 25 , 26 ]. For the consumer, the quality of spice is determined by its seasoning properties (the smell and taste giving and improving in different dishes).…”
Section: Characteristics Of Selected Spices and Its Relevance To The ...mentioning
confidence: 99%